Perceived Factors Affecting the Integration-Responsiveness Framework: An Analysis from Chinese Multinationals Operating in Australia - Fan, David; Zhu, C.; Nyland, C. (Canadian Center of Science and Education, 2012)
This study extends quantitative and conceptual studies that have clarified and assessed the underlying factors influencing multinational corporations (MNCs) international business strategy choices relating to global integration and local responsiveness with the use of cross–level and in-depth interviews. Top management perceptions from nine Chinese MNCs (CMNCs) with operations in Australia are detailed and it is argued a contingency approach tends to prevail within firms with organisational, industrial, and environmental contingencies predominating.